2021
DOI: 10.3390/antibiotics10030262
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Genes and Diversity of Clones among ESBL- and Acquired AmpC-Producing Escherichia coli Isolated from Fecal Samples of Healthy and Sick Cats in Portugal

Abstract: The aim of the study was to analyze the mechanisms of resistance in extended-spectrum beta-lactamase (ESBL)- and acquired AmpC (qAmpC)-producing Escherichia coli isolates from healthy and sick cats in Portugal. A total of 141 rectal swabs recovered from 98 sick and 43 healthy cats were processed for cefotaxime-resistant (CTXR) E. coli recovery (in MacConkey agar supplemented with 2 µg/mL cefotaxime). The matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) method was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 64 publications
3
19
1
Order By: Relevance
“…Regarding the Portuguese situation, the prevalence of ESBL-producing E. coli isolates in healthy dogs obtained in this work is similar to previous studies performed in dogs and cats [ 12 , 22 , 23 ] in the South and the North of Portugal. Worldwide, this prevalence was lower than the ones obtained with faecal samples of healthy dogs in Germany, Brazil, or China (24–29%) [ 15 , 37 , 38 ], but it is similar to the results of previous studies performed in Tunisia and France (12.7–17%) [ 11 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the Portuguese situation, the prevalence of ESBL-producing E. coli isolates in healthy dogs obtained in this work is similar to previous studies performed in dogs and cats [ 12 , 22 , 23 ] in the South and the North of Portugal. Worldwide, this prevalence was lower than the ones obtained with faecal samples of healthy dogs in Germany, Brazil, or China (24–29%) [ 15 , 37 , 38 ], but it is similar to the results of previous studies performed in Tunisia and France (12.7–17%) [ 11 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the CMY-2 gene was the qAmpC β-lactamase type found among two CTX R -ESBL-negative isolates and one ESBL-producing isolate, and it has been previously reported among E. coli strains from healthy and sick pets worldwide [ 20 , 23 , 39 , 44 ]. The detection of tet A and/or tet B genes in most of our tetracycline-resistant isolates seem to be similar to the results obtained by Costa et al [ 45 ] from dogs, in Northern Portugal.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In Germany, this enzyme was also the most prevalent ESBL type (around 50% of the strains investigated) [ 17 ]. Recently, the bla CTX-M-15 gene was the most frequently detected among E. coli of both sick and healthy dogs and cats in Portugal [ 14 , 15 ]. Nevertheless, the bla CTX-M-1 was the most common ESBL gene among healthy students in Portugal (Lisbon), followed by the bla CTX-M-15 gene [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies reported ESBL-producing K. pneumoniae isolates among urinary tract infections and invasive infections in patients in Portugal [ 4 , 5 , 9 ], as well as among healthy Portuguese students in Lisbon [ 13 ]. Furthermore, a previous report created by our group showed the presence of ESBL-producing E. coli among healthy and sick cats [ 14 ] and dogs [ 15 ] in Portugal.…”
Section: Introductionmentioning
confidence: 99%